Determination of Mineral, Vitamin Content and Antioxidant Activity of Telfairia Occidentalis Seed - Jabir, Abdulmumin; Siddan, Ahmad Alhassan; Dauda, Maianguwa Abdulrsashid; Umaru, Isaac John; Habibu, Bilyaminu; Oluwabunmi, Adeseye Helen; Iseko, Kingsley Iyoko; Istifanus, Dafup Katdel (Darul Yasin Al Sys, 2024)
Telfairia occidentalis, also known as fluted pumpkin, is a widely cultivated vegetable in West Africa with potential nutritional and health benefits. They serve to supplement the nutrients provided by cereals and tubers; however, there is lack of comprehensive compositional data regarding the mineral of fluted pumpkin seeds in Nigeria. This study aimed to determine the mineral, vitamin, and antioxidant properties of T. occidentalis seeds. The seeds were analyzed for their mineral content (calcium, iron, zinc, magnesium, potassium, and sodium), vitamin content (vitamins A, C, and E), and antioxidant activity using standard analytical methods. The results showed that the seeds were rich in essential minerals, especially manganese; 573.01±0.39mg/kg, sodium; 525.02±0.91mg/kg, calcium; 297.06±1.05mg/kg, iron; 53.42±0.59mg/kg and zinc; 5.65±0.01mg/kg. The seeds exhibited potent antioxidant activity, as measured by various in vitro assays. The presence of vitamin E (35.54±0.47mg/kg), vitamin C (20.20±0.44mg/kg) and vitamin A (15.17±0.16mg/kg). The low levels of antioxidant activity ferric reducing antioxidant power (0.49±0.01) and hydrogen scavenging activity (1.20±0.01) makes the fluted pumpkin (Telfairia occidentalis) safe for consumption. These findings suggest that T. occidentalis seeds could be a valuable source of nutrients and bioactive compounds with potential health-promoting properties. Further research is warranted to explore the nutritional and therapeutic applications of this underutilized seed crop.